Risk Stratification of Cytogenetically Normal Acute Myeloid Leukemia With Biallelic CEBPA Mutations Based on a Multi-Gene Panel and Nomogram Model - Wu, Li-Xin; Jiang, Hao; Chang, Ying-Jun; Zhou, Ya-Lan; Wang, Jing; Wang, Zi-Long; Cao, Lei-Ming; Li, Jin-Lan; Sun, Qiu-Yu; Cao, Shan-Bo; Lou, Feng; Zhou, Tao; et al. (Frontiers in Oncology, 2021)
Background: Approximately 30% of Chinese individuals with cytogenetically normal acute myeloid leukemia (CN-AML) have biallelic CEBPA (biCEBPA) mutations. The prognosis and optimal therapy for these patients is controversial in clinical practice. Methods: In this study, we performed targeted region sequencing of 236 genes in 158 individuals with this genotype and constructed a nomogram model based on leukemia-free survival (LFS). Risk stratification was performed by the risk factors to investigate the risk-adapted post-remission therapy. Results: At least 1 mutated gene other than CEBPA was identified in patients and mutation number was associated with LFS (61.6% vs. 39.0%, P =0.033), survival (85.6% vs. 62.9%, P =0.030) and cumulative incidence of relapse (CIR) (38.4% vs. 59.5%, P =0.0496). White blood cell count, mutations in CFS3R, KMT2A and DNA methylation related genes were weighted to construct a nomogram model and differentiate two risk subgroups. Regarding LFS, low-risk patients were superior to the high-risk (89.3% vs. 33.8%, P <0.001 in training cohort; 87.5% vs. 18.2%, P =0.009 in validation cohort). Compared with chemotherapy, allogenic hematopoietic stem cell transplantation (allo-HSCT) improved 5-year LFS (89.6% vs. 32.6%, P <0.001), survival (96.9% vs. 63.6%, P =0.001) and CIR (7.2% vs. 65.8%, P <0.001) in high-risk patients but not low-risk patients (LFS, 77.4% vs. 88.9%, P =0.424; survival, 83.9% vs. 95.5%, P =0.173; CIR, 1.7% vs. 11.1%, P =0.901). Conclusions: Our study indicated that biCEBPA mutant-positive CN-AML patients could be further classified into two risk subgroups by four factors and allo-HSCT should be recommended for high-risk patients as post-remission therapy. These data will help physicians refine treatment decision-making in biCEBPA mutant-positive CN-AML patients.